2012
DOI: 10.2527/jas.2011-5019
|View full text |Cite
|
Sign up to set email alerts
|

Organic and inorganic selenium: III. Ewe and progeny performance

Abstract: Selenium is an essential micronutrient in sheep, and deficiency can limit lamb growth and survival. To evaluate how different chemical forms of Se administered to mature ewes at comparative dosages affect ewe and progeny performance, 240 ewes were divided into 8 treatment groups (n = 30 each) and drenched weekly with no Se; at the maximum FDA-allowed concentration with inorganic Na-selenite or organic Se-yeast (4.9 mg Se/wk); with inorganic Na-selenate (8.95 mg Se/wk); or with inorganic Na-selenite and organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 26 publications
7
25
0
Order By: Relevance
“…We also observed differences in body condition scores of study ewes at week 60, as we have reported previously in a companion paper [27]. Therefore, we started to measure fecal egg counts in week 63.…”
Section: Experimental Design and Treatmentssupporting
confidence: 79%
See 2 more Smart Citations
“…We also observed differences in body condition scores of study ewes at week 60, as we have reported previously in a companion paper [27]. Therefore, we started to measure fecal egg counts in week 63.…”
Section: Experimental Design and Treatmentssupporting
confidence: 79%
“…None of the ewes receiving supranutritional Se-yeast supplements, nor their progeny, showed adverse clinical signs at any time throughout two lambing seasons. To the contrary, the progeny gained more weight in both lambing seasons and had better survival rates until weaning in the second lambing season [27]. Benefits of supranutritional Se-yeast supplementation in ewes included more rapid recovery of foot rot lesions [29], improved immune function (increased Escherichia coli killing by neutrophils, increased antibody titers to the novel antigen keyhole limpet hemocyanin, and increased neutrophil expression of genes involved in bacterial pathogen recognition and response) [30,31], and increased immunoglobulin G transfer to their offspring [32].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nutrient transfer from dam to offspring occurs via two pathways: placental transfer and colostrum/milk ingestion (Hefnawy et al, 2014). Selenium placental transfer was demonstrated by De Toledo and Perry (1985) and Stewart et al (2012) and fetal selenium concentrations have been shown to be greater (Stewart et al, 2012) than corresponding maternal selenium concentrations. Addition of Se to the maternal diet increased Se concentration in both serum and colostrum (Phipps et al, 2008;Slavik et al, 2008;Karren et al, 2010;Kachuca et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Provision of Se to the mother during pregnancy is an effective method to meet Se requirements in the newborn, R. Bras. Zootec., 46(2): [147][148][149][150][151][152][153][154][155]2017 as it efficiently passes through the placental barrier into fetal tissues and is also transferred into colostrum and milk (Rock et al, 2001;Stewart et al, 2012). A close relationship has been detected between offspring serum Se and maternal levels after feeding with Se, once the offspring obtains this nutrient via the placenta before birth (Hefnawy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%